Successful research supervision advising students doing research - Lee, Anne (London Routledge, 2020)
"The new and fully updated second edition of Successful Research Supervision offers a research-based practical framework for academics to examine and develop their effectiveness as research supervisors. By identify the optimum combination of approaches to best fit individuals this text helps supervisors to move their students towards the ultimate goal of being able to study independently in a thoughtful, coherent and efficient manner. This go-to guide for both novice and experienced supervisors takes the reader from the initial steps, to managing a project through to successful completion. Successful Research Supervision is crucial reading to all those seeking to develop their practice"--Provided by publisher.
Tomorrow's supervisor -- A framework for analysing approaches to teaching and supervision -- Theoretical background to the framework -- Functional teaching and supervision -- Supporting enculturation -- Developing critical thinking -- Enabling emancipation -- Creating a relationship -- Using the framework -- Supporting careers -- Supporting academic writing -- Dilemmas of co-supervision -- Creating the ethical researcher -- Supervising differently -- Preparing to examine research work -- Looking to the future: researching and developing research supervision skills.
Includes bibliographical references and index.
Keywords: Graduate students -- Supervision of; Faculty advisors; Dissertations, Academic